Factors influencing participation in a randomized controlled resistance exercise intervention study in breast cancer patients during radiotherapy - Gollhofer, Sandra; Wiskemann, Joachim; Schmidt, Martina; Klassen, Oliver; Ulrich, Cornelia; Oelmann-Avendano, Jan Tobias; Hof, Holger; Potthoff, Karin; Steindorf, Karen (BMC cancer, 2015)
Background: Over the past years knowledge about benefits of physical activity after cancer is evolving from randomized exercise intervention trials. However, it has been argued that results may be biased by selective participation. Therefore, we investigated factors influencing participation in a randomized exercise intervention trial for breast cancer patients. Methods: Non-metastatic breast cancer patients were systematically screened for a randomized exercise intervention trial on cancer-related fatigue. Participants and nonparticipants were compared concerning sociodemographic characteristics (age, marital status, living status, travel time to the training facility), clinical data (body-mass-index, tumor stage, tumor size and lymph node status, comorbidities, chemotherapy), fatigue, and physical activity. Reasons for participation or declination were recorded.Results: 117 patients (52 participants, 65 nonparticipants) were evaluable for analysis. Multiple regression analyses revealed significantly higher odds to decline participation among patients with longer travel time (p = 0.0012), living alone (p = 0.039), with more comorbidities (0.031), previous chemotherapy (p = 0.0066), of age ≥ 70 years (p = 0.025), or being free of fatigue (p = 0.0007). No associations were found with BMI or physical activity. By far the most frequently reported reason for declination of participation was too long commuting time to the training facility. Conclusions: Willingness of breast cancer patients to participate in a randomized exercise intervention study differed by sociodemographic factors and health status. Neither current physical activity level nor BMI appeared to be selective for participation. Reduction of personal inconveniences and time effort, e.g. by decentralized training facilities or flexible training schedules, seem most promising for enhancing participation in exercise intervention trials.
Gesehen am 21.07.2020